If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(4x + 3) + -1 = -118 Reorder the terms: 2x + 3(3 + 4x) + -1 = -118 2x + (3 * 3 + 4x * 3) + -1 = -118 2x + (9 + 12x) + -1 = -118 Reorder the terms: 9 + -1 + 2x + 12x = -118 Combine like terms: 9 + -1 = 8 8 + 2x + 12x = -118 Combine like terms: 2x + 12x = 14x 8 + 14x = -118 Solving 8 + 14x = -118 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 14x = -118 + -8 Combine like terms: 8 + -8 = 0 0 + 14x = -118 + -8 14x = -118 + -8 Combine like terms: -118 + -8 = -126 14x = -126 Divide each side by '14'. x = -9 Simplifying x = -9
| n*7=3n | | 7x-77=7777 | | 1/3x-2=22 | | A=-4-(8-6x) | | 36=12-3/2x | | -5x+20=40 | | 1/4x=1/2(50-x) | | 12x+36=24 | | cos(2x)cos(3x)=0.5 | | 2m+10=10 | | 9(6y-7)-(5y+6)= | | (2x+3)(x-5)=9 | | 6y+10x=18 | | e^-(x/2)=0 | | e^-x/2=0 | | 6y+10x=18fory | | e^x/2=0 | | 8x-7y-11=0 | | 28-6(-8)/-8(2) | | 2(x+5)+4= | | 3.8=0.5(8n-46) | | 8a-3=11 | | 5x+3(2x+-8)=9 | | 4(x-(1/2))^2 | | -3x^3+4x^2+x+6=0 | | 4c(3c^3+4)=(3c^3-4) | | 3y+1-36=12(1)+y-9 | | (5a+4b)=(5a-4b) | | (5a+4b)=(4a-4b) | | 5(16)+w-35=7w+16-49 | | 96/y/y=4 | | 4y(y)=96 |